STUDY AND MAPPING OF DEGRADATION OF THE ARALKUM DESERT - SaduovaGulmira,; Issanova Gulnura,; KakimzhanovYerkin,; Jilili Abuduwailiis , (Academic Journal of Physical and Chemical Sciences, 2020)
Desertification is a land degradation in arid, semi-arid and dry sub-humid areas as a result of various factors, including climate change and human activities. The Aral Sea is called the once large, and now almost dry, salt lake, which today looks like a large salt desert. Its drying is considered one of the greatest environmental disasters of our time, because only 50 years ago it was one of the four largest lakes on our planet. In the 1990s, the western world learned about the environmental disaster of what used to be the fourth largest lake in the world - The Aral Sea. The abrupt drying of the Aral Sea led to the intensive development of desertification processes in the region and the formation of the new man-made Aralkum desert. The main method for determining the soil degradation of the Aralkum desert is the calculation of indices. The selected methods are widely known and repeatedly applied in world practice methods for processing satellite images. So, all of the listed spectral indices are universal. The uniqueness of this technique lies in the determination of the exact ranges of values for each of the spectral indices in the identification of various indicators of desertification.